ANALISIS KINERJA PRODUKSI, HARGA POKOK PENJUALAN DAN STRATEGI OPERASIONAL AGROINDUSTRI (STUDI KASUS AGROINDUSTRI KERIPIK PISANG PANDA ALAMI DI KABUPATEN PESAWARAN) - Nabilah Rohma Balqis; Dwi Haryono; Adia Nugraha (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2022)
The research aims to analyze the production performance, determine production cost, determine selling cost and determine the priority of banana chips agroindustry operational strategy.  Respondents were the owner, employees and field workers at Dinas Perindustrian & Perdagangan in Pesawaran Regency.  Data were analyzed using a quantitative and qualitative analysis (analysis of production performance), descriptive quantitative (production cost and selling cost) and also descriptive qualitative analysis (SWOT).  The results of this research showed that production performances of banana chips agroindustry in terms of capacity, quality, delivery speed and processing speed have been good, but in terms of productivity and flexibility are still not optimal.  Price of banana chips is IDR78,782.50/kg with the determine production cost of IDR42,062.50/kg and determine selling cost IDR42,226.80/kg with profit margin of 86.57 percent.  The main strategy of priorities are (1) increasing productivity by utilizing raw materials and technology, (2) improving product quality by utilizing technology, (3) establishing partnerships with other outlets to introduce products by improving product quality, (4) utilizing technology to increase agroindustry profits, (5) owner of agroindustry determine production policies in accordance with high community needs and utilize the skills of agroindustrial human resources. (6) government support to increase production. Key words: operational strategies, production performance, selling cost